Inventory Planning Analysis for Carboxymethyl Celullosa (CMC) at PT. XYZ - Wijayanti, Tasya Aulia; Hidayah, Nur Yulianti; Akbar, Mohammad Ilhamsyah (P3M Politeknik Perkapalan Negeri Surabaya, 2025)
PT XYZ is a manufacturing company that produces clay roof tiles with one of the raw materials is Carboxymethyl Cellulose (CMC) for the glazing process. Currently, CMC inventory management faces a problem where during January-December 2023 there was an average overstock of 2,467 kg/month or Rp225,241,200/month. In order to minimize overstock and reduce inventory costs, it is necessary to analyze CMC inventory planning. Inventory analysis begins with forecasting to determine CMC requirements for the January-December 2024 period. The inventory planning methods used were Economic Order Quantity (EOQ) and Economic Order Interval (EOI). The selected forecasting method was Double Moving Average because it has the smallest forecasting error with a MAPE of 10.86% and valid MR Chart verification. The results of the analysis of total inventory costs during the period January-December 2024 using the EOQ method amounted to Rp2,139,459,931 while the EOI method amounted to Rp2,139,739,357. Based on the cost difference between the two methods, it is proven that the EOQ method is cheaper than the EOI method, and the results of the cost comparison analysis using the method used by the company is proven that if the company uses the EOQ inventory method the company will be able to save Rp7,042,779 or 0.33% per year. Thus the EOQ method is the right method in minimizing the total cost of CMC inventory and can minimize the risk of overstock.